Evaluation of fungicides used in the management of black Sigatoka in banana cultivation - Cervantes-Álava, Abrahan; Sánchez-Urdaneta, Adriana; Colmenares , Ciolys; Quevedo-Guerrero, José (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2023)
The main phytosanitary problem of commercial bananas is black Sigatoka (BS; Mycosphaerella fijiensis), which causes damage to leaf area, loss of exportable quality, and low yields. The management of BS with mixtures of four systemic fungicides in different combinations in the border and central area of three banana plantations, and its effect on the severity of this disease were evaluated. The study was carried out in Ecuador, province of El Oro, Pasaje canton, at the ‘‘El Playón’’, ‘‘Mega Impulso’’ and ‘‘Lolita’’ farms; in an area of 5 hectares of the Williams cultivar with 10 years of production, 50 plants were selected in the vegetative phase in the borders and center of the plantation, four treatments were evaluated: T1 (Triazole+Amine), T2 (Pyrimethanil+Spiroxamine), T3 (Difenoconazole+Amine) and T4 (Amine+Pyrimethanil) and three replicates, with four applications every 14 days.  Severity was assessed for 10 weeks using the Stover scale. The experimental design was a randomized block design and the data were analyzed by two-way ANOVA. The greatest fungicidal effect was achieved in ‘‘El Playón’’, the severity for leaf 4 in the border area was 37.5 % and 38 % in the center.  On leaf 5, ‘‘El Playón’’ 55 %, ‘‘Mega Impulso’’ 60 %, and ‘‘Lolita’’ 72.5 % reached a severe value. The highest average number of functional leaves was obtained in ‘‘Mega Impulso’’ and the highest average number of old leaves free of streaks in ‘‘Lolita’’. The fungicides applied controlled BS, due to the low percentages of disease severity.